Risk analysis of oil transportation from the Persian Gulf to America in connection with the Suez Canal reconstruction - Pershina Larisa (EDP Sciences, 2021)
The tonnage capacity of the Suez Canal has almost doubled since its reconstruction. The risk analysis of oil and oil products transportation is carried out in the paper, considering this factor from the Persian Gulf to America, and in order to reveal the economic efficiency of the existing recommended routes. According to the research outcomes and calculations, it is proved that the most expensive path is the route through the Suez Canal. It can be profitable on a short haul for transportation to the countries of the Mediterranean Basin and Western Europe due to the low tariff plan for small vessels of the LRl, MR, Handymax, Handysize classes and doubling the freight by reducing the transit time over short distances. An analysis of the probable routes from the Persian Gulf to North America through the Suez Canal and bypassing Africa is carried out in the paper. The economic effect calculation of oil transportation is conducted using the example of the Sea Vigor tanker of the Suezmax class through the Suez Canal and the Cape of Good Hope, considering the distance, the cost of escorting ships through the Suez Canal, the risk assessment and cost of ship security services, the calculation of wind-wave losses of routes bypassing the African continent. Besides, the conclusions and recommendations are formulated in the paper.